Penerapan Akuntansi Manajemen pada Usaha Mikro Kecil dan Menengah (UMKM) : MADU AKASIA ASLI - Rizky Ramadhan; Adrian Dimas Pratama; Ratih Kusumastuti (Trending: Jurnal Manajemen dan Ekonomi, 2024)
This study investigates how the functions and elements of management accounting are implemented. Using GENUINE ACACIA HONEY as a research subject. Primary and secondary data were used in this research. This research uses qualitative methods using interactive analysis. Data was collected directly from the owners of GENUINE AKACIA HONEY and analyzed in the field to make it more representative. The data collection method is used to collect data seen from the use of the data through observation and so on. Data must provide supporting factual information, for example from the results of (1) interviews and (2) observations. The interview was asked to the owner of GENUINE ACACIA HONEY in the form of unstructured questions. Observations are carried out directly to obtain relevant results and can also be used as a reference. The results of observations and interviews are presented in the form of tables and research questions in realizing the functions of management accounting, namely planning, controlling and decision making.